Evaluation of Some Male and Female Rats’ Reproductive Hormones Following Administration of Aspartame With or Without Vitamin C or E - Azeez, Omar H (The Iraqi Journal of Veterinary Medicine, 2021)
Aspartame (ASP) is a sugar substitute. Its use rose because it has been demonstrated to have deleterious effects after being metabolized. In the presence of antioxidant vitamins C or E, the effects of ASP on reproductive hormones of adult male and female Albino Wister rats were investigated. A total of eighty male and female rats were used in this study. The rats were divided into four groups: group 1, received no treatment; group 2, received ASP at 40 mg/kg BW; group 3, received ASP at 40 mg/kg BW with vitamin C at 150 mg/kg BW; and group 4, received ASP at 40 mg/kg BW and vitamin E at 100 mg/kg BW. All treatments were given orally by gavage needle once daily for consecutive 90 days. The levels of estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone hormone (TH) were measured after 90 days in blood plasma. In comparison with the control group, ASP treatment resulted in lower levels of E2, FSH, and LH in male and female rats. When the antioxidants vitamin C or E was given, the effects of ASP were reversed, and the levels of E2, LH, and FSH were increased. The testosterone hormone was likewise significantly increased by ASP, but testosterone hormone concentrations were decreased by vitamin C or E treatments. Long-term ASP consumption caused interfering with testicular and ovarian hormonal activity, while vitamins C and E on the other hand, overcome longstanding consumption ASP's effects.